The Value and Potential Integration of Pharmacy Technician National Certification into Processes That Help Assure a Competent Workforce - Shane P. Desselle; Kenneth C. Hohmeier; Kimberly C. McKeirnan (MDPI AG, 2019)
The purposes of this study were: (1) to determine pharmacists’ perceptions of the impact of certification on competence in specific job skills, its impact in combination with job experience, and its impact in combination with other types of vocational education/training; (2) to identify elements that could potentially enhance the value, or impact of national certification; and (3) to determine how pharmacists view certification in light of various personnel management and organizational behavior phenomena. A self-administered survey was constructed and delivered in spring of 2019 to a random sample of four U.S. states chosen for their geographic diversity and relatively high proportions of both certified and non-certified pharmacy technicians. Following multiple reminders, a response rate of 19.3% was obtained. The 326 responding pharmacists saw certification being less impactful alone than when combined with other types of education/training and previous job experiences. They saw the need for more skills-related and “soft skills” content on the certification examination and agreed that certification is a factor in hiring decisions and that it should be required for designation for advanced practice status. Taken together, respondents saw the need for pharmacy leaders to integrate certification with other aspects of preparation to make for a more competent and professional workforce support team.